Design and Construction of the Barbershop Start up Application Using the Lean Startup Method for the Palembang City Area - Qois Al Qorni; Agung Setiaji; Tata Sutabri (Jurnal Info Sains : Informatika dan Sains, 2023)
Nowadays, hair care is one of the appearance factors which must be kept by the men. This is proven by the large number of people opening salon businesses specifically for men or it could be called barbershops. So far, if we want to get a haircut or go to a barbershop, we always come to the barbershop location and have to queue. From these problems the idea has been arrived to build an Android-based barbershop startup application. By building an Android-based barbershop application, it is hoped that it will be a solution to this problem so that users can book or order a barbershop online without coming to Barbershop and waiting in line. This research aims to design a barbershop startup application that is capable of providing interaction between users and barbershop entrepreneurs so that users do not have to come and queue at the barbershop. The barbershop startup application was built using the lean startup method by focusing on fast prototype creation. This application system used Android Studio software. By building this application, users can save time without coming directly to the barbershop, just order online, and barbershop entrepreneurs can improve the quality of service and income.